At the heart of the Empire : Indians and the colonial encounter in late-Victorian Britain - Burton, Antoinette M., 1961- (University of California Press, 1998)
"In this study, Antoinette Burton investigates the colonial empire through the eyes of three of its Indian subjects. The first of these, Pandita Ramabai, arrived in London in 1883 to seek a medical education. She left in 1886, having resisted the Anglican Church's attempts to make her an evangelical missionary, and began a career as a celebrated social reformer. Cornelia Sorabji went to Oxford to study law and became one of the first Indian women to be called to the bar. Already a well-known Bombay journalist, Behramji Malabari traveled to London in 1890 to seek support for his social reform projects. All three left the influence of imperial power keenly during even the most everyday encounters in Britain, and their extensive writings are conscious analyses of how "Englishness" was made and remade in relation to imperialism." "Written clearly and persuasively, this historical treatment of the colonial encounter challenges the myth of Britain's insularity from empire, demonstrating instead that the United Kingdom was a terrain open to contest and refiguration."--Jacket